A Pilot Randomized Clinical Trial of a Novel, Culturally Adapted, Trauma-Focused Cognitive-Behavioral Intervention for War-Related PTSD in Iraqi Women. Issue 4 (July 2022) - Zemestani, Mehdi; Mohammed, Ako Faiq; Ismail, Azad Ali; Vujanovic, Anka A.
Highlights: Trauma-focused CBT (TF-CBT) for PTSD was culturally adapted for Kurdish women in Iraq. A randomized clinical trial was conducted to test the efficacy of culturally adapted TF-CBT. Cultural adaptations of TF-CBT included anecdotal folklores and religious traditions. Culturally adapted TF-CBT significantly reduced PTSD, depression, anxiety, and stress symptoms. Culturally adapted TF-CBT increased quality of life at posttreatment and 1-month follow-up. Abstract: Trauma-focused cognitive-behavioral therapy (TF-CBT), broadly, is one of the leading evidence-based treatments for youth with posttraumatic stress disorder (PTSD). Generally, few culturally adapted TF-CBT interventions have been examined among war trauma-affected populations in low- and middle-income countries. Using a randomized clinical trial design, a total of 48 war trauma-exposed women in Iraq, M age ( SD ) = 32.91 (5.33), with PTSD were randomly assigned to either TF-CBT or wait-list control (WLC) conditions. The intervention group received 12 individual weekly sessions of a culturally adapted TF-CBT intervention. Significant reductions in PTSD symptom severity were reported by women in the TF-CBT condition from pre- to posttreatment. Women in the TF-CBT condition reported significantly greater reductions in PTSD symptoms compared to WLC at 1-month follow-up. Additionally, levels of depression, anxiety, stress, and use of maladaptive emotion regulation strategies were significantly lower in the TF-CBT condition at posttreatment and 1-month follow-up, compared to the WLC condition. Women in the TF-CBT condition also reported significant improvements in various domains of quality of life at posttreatment and 1-month follow-up. This clinical trial provides preliminary cross-cultural support for the feasibility and efficacy of TF-CBT for the treatment of PTSD symptoms among women in non-Western cultures. Future directions and study limitations are discussed.